Evaluation of Home Healthcare Services By Service Providers and Users - KÜÇÜK, Yavuz Selim; Şahin, Bayram (YCAB Publisher, 2024)
Background: On May 15, 2017, the Turkish Ministry of Health transferred the coordination and delivery of home healthcare services from primary healthcare facilities to hospitals. Objective:This study aims to find out what the patients, their families, and home healthcare providers think about this organizational change that has been made to the service delivery process. Methods: In the quantitative research, the survey created using the results of qualitative research was administered to 396 individuals, comprising 322 patients or their relatives and 74 medical staff members. The survey's reliability was assessed using Cronbach's alpha coefficient, its validity was assessed using exploratory and confirmatory factor analyses, and the t-test was used to test the hypotheses. Results: Following the transfer of home health service delivery and coordination from primary healthcare institutions to hospitals, it was found that visit frequency-satisfaction, equity, monitoring-evaluation, and socio-economic support were the dimensions in which patients and their relatives participated more than healthcare personnel. However, compared to patients or patient relatives, healthcare personnel participate more in the areas of access to services, personnel-financial support, and private sector-security support. Conclusions: According to these findings, it is noteworthy that both groups have a much higher level of participation in issues that directly concern them. Thus, it is believed that improving the problems that clients and staff find objectionable will enhance home health services. Keywords: Home care; healthcare providers; healthcare users; primary healthcare; hospitals